Circulation Driven by Multihump Turbulent Mixing Over a Seamount in the South China Sea - Ye, Ruijie; Shang, Xiaodong; Zhao, Wei; Zhou, Chun; Yang, Qingxuan; Tian, Zichen; Qi, Yongfeng; Liang, Changrong; Huang, Xiaodong; Zhang, Zhiwei; Guan, Shoude; Tian, Jiwei (Frontiers in Marine Science, 2022)
Turbulent mixing above rough topography is crucial for the vertical motions of deep water and the closure of the meridional overturning circulation. Related to prominent topographic features, turbulent mixing not only exhibits a bottom-intensified vertical structure but also displays substantial lateral variation. How turbulent mixing varies in the upslope direction and its impact on the upwelling of deep water over sloping topography remains poorly understood. In this study, the notable multihump structure of the bottom-intensified turbulent diffusivity in the upslope direction of a seamount in the South China Sea (SCS) is revealed by full-depth fine-resolution microstructure and hydrographic profiles. Numerical experiments indicate that multihump bottom-intensified turbulent mixing around a seamount could lead to multiple cells of locally strengthened circulations consisting of upwelling (downwelling) motions in (above) the bottom boundary layer (BBL) that are induced by bottom convergence (divergence) of the turbulent buoyancy flux. Accompanied by cyclonic (anticyclonic) flow, a three-dimensional spiral circulation manifests around the seamount topography. These findings regarding the turbulent mixing and three-dimensional circulation around a deep seamount provide support for the further interpretation of the abyssal meridional overturning circulation.